1988
DOI: 10.1016/0735-1097(88)90422-6
|View full text |Cite
|
Sign up to set email alerts
|

Results of balloon valvuloplasty in typical and dysplastic pulmonary valve stenosis: Doppler echocardiographic follow-up

Abstract: To assess the usefulness of balloon valvuloplasty in patients with a dysplastic pulmonary valve, the files of 36 patients (aged 1 day to 18.5 years) who had two-dimensional echocardiography before and continuous wave Doppler echocardiography late after balloon valvuloplasty (balloon diameter greater than or equal to 20% anulus diameter) were reviewed. Results of relief of pulmonary stenosis were graded by catheter gradient in the catheterization laboratory and compared with Doppler echocardiographic findings a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 11 publications
2
19
0
Order By: Relevance
“…Its use in patients with a dysplastic valve is much less established, although several authors have suggested situations wherein it may be feasible. 408,409 Postoperative valvular, conduit, or homograft stenosis contributes to the causes of clinical RVOT obstruction, with valvular degeneration expected after approximately 10 to 12 years. 410 There are some data showing that porcine valves may outlast homografts in children.…”
Section: (Level Of Evidence: C)mentioning
confidence: 99%
“…Its use in patients with a dysplastic valve is much less established, although several authors have suggested situations wherein it may be feasible. 408,409 Postoperative valvular, conduit, or homograft stenosis contributes to the causes of clinical RVOT obstruction, with valvular degeneration expected after approximately 10 to 12 years. 410 There are some data showing that porcine valves may outlast homografts in children.…”
Section: (Level Of Evidence: C)mentioning
confidence: 99%
“…12,13 Some guidelines regarding which valves may be more or less favorable for balloon dilation in pulmonary valve dysplasia have been suggested by a number of authors. [133][134][135] Balloon pulmonary valve dilation has been used successfully in patients with tetralogy of Fallot and other forms of cyanotic heart disease in which valvular pulmonic stenosis is an important feature. Although there appears to be some additional risk involved with using these procedures due to the potential of initiating hypercyanotic episodes, the overall results are encouraging.…”
Section: Balloon Dilation Of Cardiac Valves Pulmonary Valve Stenosismentioning
confidence: 99%
“…17 Long-term follow-up showed that; 6 months of postoperative, the systolic pressure gradient across the pulmonary valve stabilized; 20 right ventricular hypertrophy and right ventricular enlargement gradually reduced; Generally PBPV postoperative 6 to 12 months, right ventricular diastolic function returns to normal, 19 long-term effectiveness was same in comparison with surgical operation. 21 Overall, the hospital stay, postoperative ICU monitoring time, the average operation time-consuming and postoperative complications and mortality, etc of PBPV are significantly lower than the surgery.…”
Section: Complications Of Pbpv Operationmentioning
confidence: 97%